Relationship between postoperative hypothalamic injury and water and sodium disturbance in patients with craniopharyngioma: A retrospective study of 178 cases - Du, Can; Leng, Yueshuang; Zhou, Quanwei; Xiao, Ju-Xiong; Yuan, Xian-Rui; Yuan, Jian (Frontiers in Endocrinology, 2022)
Objective: To investigate the relationship between postoperative hypothalamo–hypophyseal injury (HHI) and postoperative water and sodium disturbances (WSDs) in patients with craniopharyngioma. Methods: The medical records, radiological data, and laboratory results of 178 patients (44 children and 134 adults) who underwent microsurgery for craniopharyngioma in a single center were reviewed. Postoperative HHI was assessed using magnetic resonance imaging (MRI). Structural defects of hypothalamo-hypophyseal system(pituitary, pituitary stalk, floor and lateral wall of the third ventricle) were assessed in four standard T1-weighted images. Defect of each structure would be assigned 1 score(0.5 for the unilateral injury of third ventricle wall) and a HHI score was calculated. Results: Number of patients had HHI score of 0-1, 2, 2.5-3, and >3 was 35, 49, 61, and 33, respectively. Diabetes insipidus (DI) worsened in 56(31.5%) patients who had preoperative DI, while 119(66.9%) patients were diagnosed with new-onset DI. Hypernatremia and hyponatremia developed in 127(71.3%) and 128(71.9%) patients after surgery, respectively. Syndrome of inappropriate antidiuresis (SIAD) occurred in 97(54.5%) patients. During hospitalization, hypernatremia recurred in 33(18.5%) patients. DI persisted in 140(78.7%) patients before discharge. A total of 54 (35.7%) patients had hypernatremia during follow-up, of whom 18 (11.9%) had severe hypernatremia. No relationship was found between the HHI score and incidence of early DI, hyponatremia, syndrome of inappropriate diuretic hormone, or prolonged DI. Compared with patients with a score of 0–1, those with score =2.5-3(OR = 5.289, 95% CI:1.098-25.477, P = 0.038) and score>3 (OR = 10.815, 95% CI:2.148-54.457, P = 0.004)had higher risk for developing recurrent hypernatremia. Patients with an score >3 had higher risk of developing severe hypernatremia both during hospitalization(OR = 15.487, 95% CI:1.852-129.539, P = 0.011) and at follow-up(OR = 28.637, 95% CI:3.060-267.981, P = 0.003). Conclusions: The neuroimaging scoring scale is a simple tool to semi-quantify HHI after surgery. The occurrence of recurrent and severe hypernatremia should be considered in patients with a high HHI score (>2.5). An HHI score >3 is a potential predictor of development of adipsic DI. Preventive efforts should be implemented in the perioperative period to reduce the incidence of potentially catastrophic complications.